Tuesday

July 29, 2014

July 29, 2014

Posted by **Mallory** on Sunday, March 11, 2007 at 7:03pm.

Given that

hx^3 - 12x^2 - x + 3=(2x-1) (2x+1) (x-k)

find the values of the constants k and h

don't even know where to start

start by expanding the right side.

then you have

hx^3 - 12x^2 - x + 3 = 4x^3 - 4kx^2 - x + k

By comparing "like" terms, h would be 4 and k would be 3

**Related Questions**

Mathematics - Kinda lost with this one Given that hx^3 - 12x^2 - x + 3=(2x-1) (...

CORE MATHS - The first two terms in the expansion of (1+ax/2)^10 + (1+bx)^10 in ...

add maths - Functions f and g are defined by f:x→ax-b,where a and b are ...

Algebra - The function h is is defined below. h(x)=48x^2+ 12x - 16 Find all ...

add maths - Function f and g are defined by f:x→4-x and g:x→px^2+q ...

Maths - It is given a quadratic function y=a(x-h)62+k.If its graph is a parabola...

maths - The method for completing the square can be used to write the expression...

chemistry - The skeletal structures of the two amino acids, glycine and lysine, ...

calculus - Given the function h : x -> 3x + c and h^-1 : x -> cx/m - 1, ...

math - Given f(x)=2-3x and g(x)=hx+k where h and k are constants.If gf(-1)=6 and...